Training on Utilization of Plastic Waste and Banana Bark Become an Economical Value Innovation Product - Yohana, Corry (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
The purpose of this community service is to provide training to communities around the TPA In South Tangerang regarding the utilization of waste to be a product of economic value as an innovative way to help the government in the management of waste as well as increase income for every familyThe method used is classical method with discussion / question and answer approach, simulation and practice of making the product, with the intention that the material can be accepted by the participants well. Guidance / consultation is done through the last session with participants, as well as by telephone or by mail. The results of the training show the participants so have the knowledge in managing waste and skills in utilizing waste to make products of economic value. It can be concluded that participants want continuous knowledge. It is desirable to provide knowledge in the form of regular training and sustainable.